A REVIEW ARTICLE ON KRIMI WITH CONTEMPORARY ASSESSMENT - Jena, *Banashree; Nanda, Gopal C; Bihari Khuntia, Bipin (International Journal of Ayurveda and Pharma Research, 2018)
Krimi exist its importance in Medical science from ages. Starting from Rig Veda to Samhita Krimi is accepted as a causative factor of diseases. Though there is mention of non-pathological Krimi in the texts, but elaboration not done. Whereas, there is wide narration of pathological Krimi found in different Samhita. Description of etiologies, habitat, nomenclature, morphology, and clinical conditions produced due to Krimi is done by different Acharyas. The clinical conditions produced due to Krimi in host may be broadly categorized under GIT ailments, skin ailments and features of Anemia. Regarding management of Krimi, there is sufficient explanation of treatment principles in Samhita. Various research works have been done concerning treatment aspects of Krimi. These clinical studies emphasize the effect of herbal, mineral or herbomineral drug preparations on certain parasite or protozoan. Only few studies have been done in Ayurveda to find out the type of Krimi infection/infestation based on the division of Krimi. Some research workers had tried to correlate the Krimi with few parasites only. The correlation of Krimi with the contemporary infectious microbes may be done by examining the resemblance of their habitat, morphology and effect on host. But it is a difficult task to correlate Krimi with modern due to lack of detail description of individual Krimi. Under the word Krimi all micro organisms like bacteria, virus, parasite, and fungus can be included. In this article effort has been made to describe the concept of Krimi from different Ayurvedic treatises and also to correlate them with similar microbes and parasites based on their habitat and effect on human body.